A SEMIOTIC ANALYSIS OF SIGNS FOUND IN MR.DIY CITAYAM CENTER - Zahira Rizka Anjani; Diva Shafira Nurhaliza (Cahaya Ilmu Bangsa Institute, 2024)
This research focuses on investigating the meaning or idea of ​​signs at the MR.DIY Citayam Center using Peirce’s Triadic model. Using descriptive qualitative method, this research explores how signs can be interpreted and understood through their representamen, object, and interpretant. A total of 30 signs were analyzed, revealing their role in guiding customer behavior, ensuring safety, and enhancing the shopping experience. The findings highlight the effective use of iconic, indexicalm and symbolic signs in communcationg store policies and operational instructions. This study demonstrates the relevance of semiotic in understanding visual communication within modern retail spaces, contributing to a broader comprehension of how signs shape consumer interactions.